Belonging in the Land: Land, Landscape, and Image in Southern African Missionary Encounters ca. 1840–1915 - Brown, Clare (Mission studies, 2018)
To choose a missionary life is to become a stranger at home and abroad, whilst at the same time attempting to construct new networks of belonging. Missionaries have at times identified profoundly with the “foreign,” through economic and political solidarity, or linguistic and cultural immersion, but mission conversely necessitates the attempt to draw the foreign Other into the sphere of Christian fraternal belonging. This paper employs primary textual and visual sources to explore the complex theme of missionary identity and belonging through the lens of landscape. Landscape and its images influenced and were utilized by missionaries, functioning as tokens of belonging, interpretative tools, and sites of territorial possession for example through burial. For indigenous peoples, missionary images of place could also betoken otherness, and conflict with alternative expressions of rooted belonging, for instance in the use of earth as part of the physical substance of indigenous religious art.